Platelet polyphosphates: The nexus of primary and secondary hemostasis - MÜLLER, Felicitas; RENNE, Thomas (Scandinavian journal of clinical and laboratory investigation, 2011)
Abstract For decades it has been known that activated platelets promote plasma clotting and that the fibrin forming activity of activated platelets is dependent on blood coagulation factor XII. However, because factor XII deficiency is not associated with any bleeding disorder, platelet-driven factor XII activation was believed to be an in vitro artefact with no importance for coagulation in vivo. Using arterial and venous thrombosis models in factor XII deficient mice we recently demonstrated that factor XII is essential for thrombosis in vivo. However it was not known how factor XII is activated by procoagulant platelets within the growing thrombus. Here, we review our studies of the last 5 years that led to the identification of the endogenous factor XII activator. We found that platelets release polyphosphates, linear inorganic polymers of 60-100 phosphate residues that directly bound to and activated factor XII. Platelet polyphosphates potently initiate fibrin formation via the factor XII-driven intrinsic pathway. Inhibition of factor XII or polyphosphates protected mice from lethal thrombotic disease and strongly reduced clot stability in patients. Our data identify polyphosphates as the endogenous factor XII activator in vivo linking platelet activation (primary hemostasis) and fibrin production (secondary hemostasis). Targeting polyphosphate-mediated factor XII activation offers the exciting possibility for a safe anticoagulation with minimal therapy-associated bleeding.